Perlakuan Ahli Waris Non Muslim Dalam Sengketa Waris Di Peradilan Agama - Afrohatul Laili, Afrohatul; Miftahus Sururi, Endri (Universitas Nahdlatul Ulama Blitar, 2023)
The authority of the Religious Courts in adjudicating inheritance disputes between people of different religions (Muslims and non-Muslims) is still questioned, especially by non-Muslim citizens, because based on the provisions of article 49 of Law Number 50 of 2009 the Religious Courts only have the authority to hear certain civil cases in between people who are Muslim and implemented based on Islamic law. This question conveys the understanding that Islamic law does not give non-Muslim heirs the right to inherit. This research uses normative research because the research uses library materials as the main data for analyzing cases. This research specifically examines the treatment of non-Muslim heirs in inheritance disputes in religious courts. In decision number 368 K/AG/1995 it is stated that non-Muslim heirs get a share of the inheritance of Muslim heirs based on a mandatory will equal to the share of Muslim heirs, in this decision non-Muslim heirs are not declared as heirs, and get the same share as Muslim heirs based on a mandatory will, in this decision it is stated that non-Muslim heirs are considered as heirs.